To Improve Students’ Listening Skill by Using Animation Video at SMAN 1 Stabat Kabupaten Langkat - Maulida Gustika; Tampubolon, Sahlan; Sinambela, Erika (The Explora, 2024)
Animation video is an alternative media to teach listening at senior high-level students. The purpose of this study to improve the listening skill of eleventh-grade students at SMA Negeri 1 Stabat at Kabupaten Langkat in the academic year 2024/2025. This study used a classroom action research method by applying animation video as an alternative teaching media. The population of this study is the eleventh-grade students consists of ten classes with a total number is 351 students. The sample of this study is 36 students (XI IPA 1). The researchers used purposive sampling to achieve the aim of study. To collect the data the researchers distributed multiple choice of listening test. The finding of this research showed that in pre-test, the students got mean score 43,75. In cycle 1, the mean score is 48,6. In cycle 2, the mean score is 60,5 or categorized moderate. In post-test, the mean score is 75,8 categorized good. So, it can be concluded that the use of animation video improved the eleventh-grade students’ listening skill at SMA Negeri 1 Stabat Kabupaten Langkat.